Discovery Service for Engineering and Technology Literature through Google Custom Search: A Case Study - Gavali, Rajashree (DESIDOC Journal of Library & Information Technology, 2015)
Discovery service in libraries has gained momentum in recent years owing to the influence of search giants like Google. Library users are expecting one search solution in similar lines with Google search engine to retrieve information from different sources, viz., library catalogue, bibliographic and full text databases, open access resources, etc. To meet this demand, new age discovery tools such as Summon and Knimbus have emerged and libraries are increasingly subscribing to such services to maximise use of electronic resources. There are also some open source tools, but their deployment is not widely seen in libraries. In this paper an attempt has been made to explain, how Google Custom Search Engine (GCSE) can be used as discovery service for subscribed, un-subscribed and open access resources. http://dx.doi.org/10.14429/djlit.35.6.8825